The Unreliability of Traditional Writing Tests - Kirkman, John (Technical Communication, 1974)
EXPERIENCED PRACTITIONERS in the technical writing business are inclined to believe that they know a good piece of writing when they see one. Among these practitioners, however, there is little agreement on what is good or bad. This article, based on Professor Kirkman's research on writing tests, suggests that we should recognize the weaknesses of subjective assessment and should minimize their effects. In the next issue of Technical Communication, a sequel by Professor Kirkman, "Compiling Objective Tests of Technical Writing Ability," will be published.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MzA4NTg2OQ